ADIYAMAN ILI SU KENESI (ACARI: HYDRACHNIDIA) FAUNASI - BEYAZ, SEDA (Fırat Üniveristesi, 2015)
Bu çalışmada, 2013-2014 yıllarında Adıyaman'dan toplanan su keneleri değerlendirilmiş ve toplam 15 familyaya ait 60 tür tespit edilmiştir. Bu türlerden; Lebertia (s.str.) cognata Koenike, 1902 ve Atractides (s.str.) gomerae Lundblad, 1962 Türkiye faunası için yeni kayıttır. Arrenurus (s.str.) cuspidifer Piersig, 1894 hariç tespit edilen türlerin tümü Adıyaman ilinden ilk defa kaydedilmiştir. Ayrıca, Türkiye için endemik olan, Lebertia (s. str.) marasensis Esen & Erman, 2015, Hygrobates (s.str.) anatolicus Peši? & Esen, 2013, Arrenurus (s.str.) ovatipetiolatus Esen & Erman, 2013 ile Kafkaslar ve Türkiye'den bilinen Brachypoda (Hemibrachypoda) orientalis Peši? & Esen, 2013 Adıyaman'dan da yakalanmıştır. Teşhis edilen tüm türlerin, morfolojik özellikleri, çeşitli organlarının ölçümleri, kısa tanımları, yaşama ortamları, Türkiye'deki ve dünyadaki yayılışları verilmiştir. Ayrıca, Türkiye Faunası için yeni kayıt olanlar ile Türkiye için endemik olan türlerin şekilleri sunulmuştur. Anahtar Kelimeler: Adıyaman, Su kenesi, Acari, Hydrachnidia, Sistematik, Türkiye.

In this study, it has been evaluated water mite species collected from Adıyaman province in 2013 and 2014 years. Totally, it has been identified 60 species belonging to 15 families. Of these, Lebertia (s.str.) cognata Koenike, 1902 and Atractides (s.str.) gomerae Lundblad, 1962 are new records for the Turkish fauna. All of the identified species, except Arrenurus (s.str.) cuspidifer Piersig, 1894, are newly recorded from Adiyaman province. Moreover, Lebertia (s. str.) marasensis Esen & Erman, 2015, Hygrobates (s.str.) anatolicus Peši? & Esen, 2013, Arrenurus (s.str.) ovatipetiolatus Esen & Erman, 2013 that are endemics for Turkey with Brachypoda (Hemibrachypoda) orientalis Peši? & Esen, 2013 that is known only from Turkey and the Caucasus have been also collected from Adiyaman Province. The morphological characters, the measurements of various organs, the short descriptions, habitats and their distributions in Turkey and all over the world of all identified species were given. Furthermore, it was also given the drawings of various organs of some species that are new records and endemics for the Turkish fauna were also given. Keywords: Adiyaman, Water mite, Acari, Hydrachnidia, Systematics, Turkey.
Water mite (Acari: Hydrachnidia) fauna of Adiyaman province
Keywords: Biyoloji